Experiencia de innovación: “Club de astronomía Orión: el conocimiento del universo al alcance de tus manos” (2015)
The inclusion of the study of astronomy in school activities, showing students how this discipline links together different areas of knowledge, was the initial idea behind the creation of a club in 2003, in the El Rodeo School, which would gather a group of teachers, children, and young students with a common interest: to learn about the universe. This type of association was established because it allowed for the development of a collaborative learning environment among its members without separating it from the academic context, which made it attractive to students. It is an experience, which is oriented, by focusing on astronomy, to contribute to the improvement of learning and the development of thinking skills in students, such as observation, experimentation, analysis, and argumentation, without distinguishing between academic levels and areas of knowledge, thanks to its specific design that transcends classroom, curriculum, school grades, and school hours. This is accomplished, in terms of methodology, by taking inquiry-based teaching as a reference point and by developing projects by students with advice from teachers. Didactically, it materializes through multiple strategies such as workshops, conferences, video-forums, participation in institutional and international projects, science fairs, recreational activities, day and night observations, and the use of astronomical softwares, among others.